PENGEMBANGAN MEDIA VIDEO ANIMASI PADA MUATAN IPS MENGGUNAKAN APLIKASI CAPCUT DI KELAS V SDN 01 KOTO BARU - Yulia Darniyanti; Muhammad Subhan; Yuliska Hoiriyanti (STKIP Subang, 2023)
Theresearch was motivated by several problems, including first, the difficulty of teachers developing animated learning video media, especially for social studies learning of Geography characteristic material in Indonesia, second, teachers find it difficult to develop media in schools, third, students are less interested in the learning process, especially social studies content because social studies learning contains many theories. One effort that can attract the attraction of students is done by developing animated video learning media that can support students to learn well. Therefore, the author is interested in developing animated video learning media using the CapCut application in elementary schools. With the aim that teachers and students have enough adequate learning media. The type of research is research and development (R&D). Research and Development is a process and research steps to develop existing products, as well as new products that can later be accounted for. Develop a product a learning video. Research and development (R&D) Research and Development (R&D) methods are used to produce a particular product and tested for effectiveness. The development model used is the development of ADDIE